Deconstrucción del antropocentrismo jurídico en el derecho constitucional ecuatoriano: análisis de las sentencias No. 253-20-JH/22 y No. 32-17-IN/21 - Montaño Escobar, Juan Carlos (2023)
The jurisprudence of the Constitutional Court of Ecuador has succeeded in issuing rulings in our judicial system, as an achievement of international reach; rulings of great importance and worth for the rights of nature such as the flora and fauna of this important and irreplaceable ecosystem, which constitutes an aspect that dignifies and enhances the current Constitution of the Republic of Ecuador. From what has been said, in this research process, after referring to this event, it will be explained the philosophical current of biocentrism, which protects human and non-human living beings; as well as anthroponcentrism, governed by the central idea that man is the centre and the end of everything, and how it is that these two currents coexist in the two selected sentences. To this end, it is the rulings contained in resolutions No. 253-20-JH/22 and No. 32-17-IN/21 issued by the Constitutional Court, which will be analysed in this text, and those that will make it possible to elaborate a deconstruction in the very fact of the incidence of anthroponcentrism in these judgments, in relation to the construction of the rulings, between majority votes and saved votes, and the origin of biocentrism, manifested in these species. Therefore, a critical but coherent criterion will be projected that is consistent with the aspiration to be able to construct an adequate argument, clearly exposing the philosophical figures described above, and how they can be present in the decisions of the Constitutional Court, when they are generated to achieve the creation of rights in favour of nature.